The Role of Economic and Social Factors in Studying and Preparing the Master Plans for the Countryside’s Villages of Latakia Governorate - Kounsselie, Georges; Saleh, Rasha (Latakia University Journal -Engineering Sciences Series, 2019)
This article examines the impact of economic and social factors in studying and preparing the organizational plans for villages and rural areas as the main pillar of the economy as an agriculture-based society. Urban Environment is produced according to organizational plans, frameworks and legal legislation that identify itself. Since each urban area (city, village) has its own distinctive character, its organizational plans must have a distinctiveness that distinguishes it from others in order to consider the socio-economic and historical factors that differ and differentiate between these regions. But the problem is that most of these villages and organized rural communities suffer from the loss of their urban, economic and social identity. And also, its organizational plans did not take into consideration these factors, and finally, there is no link between urban and architectural studies which led to a lack of expression of the needs and desires of the inhabitants of these villages and communities and placed additional burdens on them (urban fabric, high densities, high proportions of construction, etc.). The study discusses two different case studies from the countryside’s villages of Latakia governorate (the mountain village of Metn, and the coastal village of Shamiya), through which will conduct an analytical study of the impact of economic and social factors on the study and preparation of the organizational plans of these villages. Finally, the study concluded with a set of conclusions and recommendations that could contribute to the development of mechanisms for the study and preparation of the organizational plans of the countryside’s villages of Latakia governorate by considering all economic and social factors and their impact on the formulation of these schemes. يتناول البحث تأثير العوامل الاقتصادية والاجتماعية في دراسة وإعداد المخططات التنظيمية للقرى والتجمعات الريفية باعتبارها تشكل الدعامة الرئيسية للاقتصاد كمجتمع قائم على الزراعة. فالعمران ينتج وفقا لمخططات تنظيمية وأطر وتشريعات قانونية تحدد هويته, وبما أن لكل تجمع عمراني (مدينة, قرية) طابعه المميز فلا بد لمخططاتها التنظيمية أن تتمتع بخصوصية تميزها عن غيرها بحيث تأخذ بعين الاعتبار العوامل الاقتصادية والاجتماعية والتاريخية التي تختلف وتتمايز بين هذه التجمعات. لكن المشكلة تكمن في أن معظم هذه القرى والتجمعات الريفية المنظمة تعاني من فقدانها لهويتها العمرانية والاجتماعية والاقتصادية؛ حيث يلاحظ عند وضع مخططاتها التنظيمية عدم مراعاة خصوصيتها وعدم الأخذ بعين الاعتبار العوامل المؤثرة على صياغة هذه المخططات ,وأخيراً عدم الربط بين الدراسات العمرانية والمعمارية الأمر الذي أدى إلى قصور في التعبير عن حاجات ورغبات سكان هذه القرى والتجمعات وشكلت أعباء إضافية عليهم (نسيج عمراني حضري , كثافات مرتفعة , نسب بناء عالية ,...الخ). يناقش البحث حالتين دراسيتين مختلفتين من قرى ريف محافظة اللاذقية( قرية المتن ذات الطبيعة الجبلية, وقرية الشامية ذات الطبيعة السهلية ), يتم من خلالها إجراء دراسة تحليلية لتأثير العوامل الاقتصادية والاجتماعية على دراسة وإعداد المخططات التنظيمية لهاتين القريتين. يخلص البحث إلى مجموعة من النتائج والتوصيات التي يمكن أن تساهم في تطوير آليات دراسة وإعداد المخططات التنظيمية لقرى ريف محافظة اللاذقية ؛ تراعي جميع العوامل الاقتصادية والاجتماعية وتأثيرها على صياغة هذه المخططات.